Soil microbiome perturbation impedes growth of Bouteloua curtipendula and increases relative abundance of soil microbial pathogens - Alisiara Hobbs; Daisy Ochoa-Rojas; Christine E. Humphrey; John A. Kyndt; Tyler C. Moore (PLoS ONE, 2026)
Bouteloua curtipendula (sideoats grama) is a valuable prairie grass for livestock forage, supporting food webs of herbivorous insects, reducing soil erosion, and limiting weed infiltration in urban grasslands. Efficient establishment of B. curtipendula in prairie restorations and urban plantings could drastically improve long-term functionality of the space. Soil microbial communities have been linked to plant germination, growth, and drought tolerance in many plant species, however little is known about the factors contributing to B. curtipendula germination and early growth. In this study, we used sterilized soil to examine the impact of soil microbes on B. curtipendula growth under greenhouse conditions. We found Bouteloua curtipendula emergence and growth to be impaired in sterilized soil compared to not-sterilized soil. Using high throughput sequencing of the soil, we found that B. curtipendula grown in sterilized soil induced a greater proportion of plant pathogens and fewer nitrifying bacteria as compared to when grown in not-sterilized soil. For example, there was a significantly higher proportion of Acidovorax , Cellvibrio , and Xanthomonas which are known to contain plant pathogens, while plant-growth promoting bacteria, like Rhodopseudomonas, were significantly higher in the not-sterile soil conditions. We found that soil sterilization and growth of B. curtipendula changed the relative abundance of metabolic subsystem genes in the soil, however, by seven weeks after seeding, B. curtipendula transformed the bacterial community of sterile soil such that it was indiscernible from not-sterile soil. In contrast, fungal communities in sterilized soil were still different from not-sterilized soil seven weeks post-seeding. It appears that the bacteria are involved in the initial establishment of beneficial conditions that set the stage for a robust fungal and plant seedling development.